Inguinoscrotal extension of a pancreatic collection: a rare complication of pancreatitis-case report and review of the literature. - Skouras,C; Skouras,T; Pai,M; Zacharakis,E; Spalding,D (Updates Surg, 2013)
Pancreatitis associated with the extension of a pancreatic collection, pseudocyst or abscess into the groin is a rare phenomenon with few reports in the English literature. Nevertheless, it remains a clinically important differential diagnosis as it may be mistaken for more common pathologies in the groin and with a subsequent unnecessary surgical intervention. A case of this rare complication of pancreatitis is reported, together with a review of the literature.